Electrochemical device and electronic equipment

CN224908038UActive Publication Date: 2026-10-27ZHEJIANG LIWINON ENERGY TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202522067717.4
Authority / Receiving Office
CN · China
Patent Type
Utility models(China)
Current Assignee / Owner
Filing Date
2025-09-25
Publication Date
2026-10-27
Estimated Expiration
2035-09-25

AI Technical Summary

Technical Problem

在电化学结构制造过程中,裸电芯的头部和尾部往往容易积累电解液,特别是在跌落冲击时,这些区域容易发生电解液移动和积聚,增加了内短路的风险

Benefits of technology

[0006]根据本申请实施例的电化学装置,至少具有如下有益效果:靠近电极组件的较大孔径的多孔层能够快速吸收积聚的电解液,而远离电极组件的较小孔径的多孔层通过更强的毛细作用力将电解液向外迁移,加速电解液在头部、尾部的扩散,提高电解液渗透效率。电解液在梯度孔层中依次通过不同孔径层时,受到逐渐增强的毛细力驱动,形成从大孔径区域向小孔径区域的定向流动,避免电解液在单一孔隙结构中的无序扩散,使得电解液在电极组件端部区域的分布趋于均匀,避免形成局部干区。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN224908038U_ABST
    Figure CN224908038U_ABST
Patent Text Reader

Abstract

The application discloses an electrochemical device and an electronic equipment, wherein the electrochemical device comprises an electrode assembly and a penetration structure, and the head and / or tail of the electrode assembly is provided with the penetration structure; one side of the penetration structure is provided with a gradient pore layer, the gradient pore layer comprises a plurality of porous layers, and each porous layer is internally provided with adsorption pores; along the length direction away from the electrode assembly, in any two adjacent porous layers, the size of the adsorption pores in the porous layer close to the electrode assembly is A, the size of the adsorption pores in the porous layer away from the electrode assembly is B, and A>B is satisfied. The electrochemical device can drive the electrolyte to be driven by gradually enhanced capillary adsorption force when the electrolyte sequentially passes through different pore size layers by the change of the pore size of the adsorption pores in the gradient pore layer, forms directional flow from a large pore size area to a small pore size area, accelerates the diffusion of the electrolyte at the head and tail, improves the penetration efficiency of the electrolyte, and makes the electrolyte tend to be uniformly distributed in the end area of the electrode assembly, thereby avoiding the formation of a local dry area.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of electrochemical energy storage technology, and in particular to electrochemical devices and electronic equipment. Background Technology

[0002] Lithium-ion electrochemical structures typically include a positive electrode, a negative electrode, a separator, and an electrolyte, all encapsulated within an electrochemical structure housing. During the manufacturing process, electrolyte tends to accumulate at the head and tail of the bare cell, especially during drop impacts, where electrolyte movement and buildup in these areas increase the risk of internal short circuits.

[0003] In related technologies, porous material layers are usually set at the head and tail of the bare battery cell to naturally adsorb the accumulated electrolyte. However, when the electrolyte diffuses naturally within the porous material layer, the permeation path is unstable, the permeation efficiency is low, and uniform distribution cannot be achieved. Utility Model Content

[0004] The main purpose of this invention is to propose an electrochemical device and electronic equipment, which aims to achieve directional penetration of electrolyte and improve the uniformity of the penetration effect.

[0005] To address the above problems, this application provides an electrochemical device, comprising: A permeable structure with a gradient pore layer on one side, the gradient pore layer comprising multiple porous layers, each of which contains adsorption pores. The electrode assembly has the aforementioned permeation structure at its head and / or tail. Wherein, along the length direction away from the electrode assembly, in any two adjacent porous layers, the size of the adsorption pore in the porous layer closer to the electrode assembly is A, and the size of the adsorption pore in the porous layer away from the electrode assembly is B, satisfying that A is greater than B.

[0006] The electrochemical device according to the embodiments of this application has at least the following beneficial effects: the porous layer with a larger pore size near the electrode assembly can quickly absorb the accumulated electrolyte, while the porous layer with a smaller pore size away from the electrode assembly uses stronger capillary forces to migrate the electrolyte outward, accelerating the diffusion of the electrolyte at the head and tail, and improving the electrolyte penetration efficiency. When the electrolyte passes through different pore size layers in the gradient pore layer, it is driven by gradually increasing capillary forces, forming a directional flow from the large pore size region to the small pore size region, avoiding the disordered diffusion of the electrolyte in a single pore structure, making the distribution of the electrolyte in the end region of the electrode assembly more uniform, and avoiding the formation of local dry areas.

[0007] In some embodiments, the porosity of the adsorption pores in each level of the porous layer is 30% to 50%.

[0008] In some embodiments, the gradient pore layer further includes an adsorption conditioning layer disposed on the side of the gradient pore layer away from the electrode assembly; The contact angle between the adsorption conditioning layer and the electrolyte is set to be inversely proportional to the volume of the electrolyte in contact with the adsorption conditioning layer.

[0009] In some embodiments, the adsorption conditioning layer is configured as a composite coating of polyvinylidene fluoride and nano-silica.

[0010] In some embodiments, the electrochemical device further includes a housing, within which the electrode assembly is disposed; The permeation structure further includes a support layer disposed on the side of the gradient pore layer opposite to the electrode assembly, and the support layer is in contact with the housing.

[0011] In some embodiments, the support layer includes multiple support ribs, which are arranged in an interlaced manner to form a grid structure.

[0012] In some embodiments, the width of the support rib is 15 μm to 30 μm, and the thickness of the support rib is 5 μm to 15 μm; The support layer has multiple mesh openings, with each side of the mesh opening having a length of 100μm to 200μm.

[0013] In some embodiments, the contact angle between the support layer and the electrolyte is greater than or equal to 70°.

[0014] In some embodiments, the permeation structure includes a first part and a second part, the second part being connected to the edge of the first part, the first part being disposed at the head and / or tail of the electrode assembly, and the second part being disposed at the outer periphery of the electrode assembly.

[0015] This application also provides an electronic device, which includes the electrochemical device described herein.

[0016] The electronic device according to the embodiments of this application has at least the following beneficial effects: by applying the above-mentioned electrochemical device, when the electrolyte passes through different pore size layers in the gradient pore layer, it is driven by gradually enhanced capillary force, forming a directional flow from the large pore size region to the small pore size region, avoiding the disorderly diffusion of the electrolyte in a single pore structure, making the distribution of the electrolyte in the end region of the electrode assembly tend to be uniform, and avoiding the formation of local dry areas.

[0017] Additional aspects and advantages of this application will be set forth in part in the description which follows, and in part will be obvious from the description, or may be learned by practice of this application. Attached Figure Description

[0018] The present application will be further described below with reference to the accompanying drawings and embodiments, wherein: Figure 1 This is a schematic diagram of the structure of an electrochemical device in one embodiment of this application; Figure 2 This is a schematic diagram of the layer structure of the permeation structure in one embodiment of this application.

[0019] Figure label: 100. Electrode assembly; 200. Permeation structure; 201. First part; 202. Second part; 210. Porous layer; 220. Adsorption conditioning layer; 230. Support layer; 300. Shell. Detailed Implementation

[0020] To make the objectives, technical solutions, and advantages of the embodiments of this application clearer, the technical solutions in the embodiments of this application will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of this application, not all embodiments. Based on the embodiments of this application, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this application. The embodiments of this application may omit unnecessary detailed descriptions. For example, detailed descriptions of well-known matters and repeated descriptions of actually identical structures may be omitted. This is to avoid making the following description unnecessarily lengthy and to facilitate understanding by those skilled in the art.

[0021] In this application, the technical features described in an open-ended manner include both closed-ended technical solutions consisting of the listed features and open-ended technical solutions that include the listed features. As used herein, the terms "generally," "substantially," and "about" are used to describe and explain minor variations.

[0022] When used in conjunction with an event or situation, the term may refer to examples in which the event or situation occurred precisely and examples in which the event or situation occurred very approximately. For example, when used in conjunction with numerical values, the term may refer to a range of variation less than or equal to ±10% of the numerical value, such as less than or equal to ±5%, less than or equal to ±4%, less than or equal to ±3%, less than or equal to ±2%, less than or equal to ±1%, less than or equal to ±0.5%, less than or equal to ±0.1%, or less than or equal to ±0.05%. For example, if the difference between two numerical values ​​is less than or equal to ±10% of the average of the values ​​(e.g., less than or equal to ±5%, less than or equal to ±4%, less than or equal to ±3%, less than or equal to ±2%, less than or equal to ±1%, less than or equal to ±0.5%, less than or equal to ±0.1%, or less than or equal to ±0.05%), then the two numerical values ​​can be considered "substantially" the same.

[0023] Furthermore, for ease of description, "first," "second," "third," etc., can be used in this article to distinguish different components of a figure or a series of figures. "First," "second," "third," etc., are not intended to describe the corresponding components.

[0024] Additionally, quantities, ratios, and other numerical values ​​are sometimes presented in range format herein. It should be understood that such range format is for convenience and brevity and should be interpreted flexibly to include not only numerical values ​​explicitly specified as range limits, but also all individual numerical values ​​or subranges covered within the range, as if each numerical value and subrange were explicitly specified. In the detailed description and claims, a list of items connected by the terms “one of,” “among,” “one of,” or other similar terms may mean any of the listed items. For example, if items A and B are listed, the phrase “one of A and B” means only A or only B. In another instance, if items A, B, and C are listed, the phrase “one of A, B, and C” means only A; only B; or only C. Item A may contain a single element or multiple elements. Item B may contain a single element or multiple elements. Item C may contain a single element or multiple elements.

[0025] In the detailed description and claims, the list of items connected by the term "at least one of" can mean any combination of the listed items. For example, if items A and B are listed, then the phrase "at least one of A and B" means only A; only B; or A and B. In another example, if items A, B, and C are listed, then the phrase "at least one of A, B, and C" means only A; or only B; only C; A and B (excluding C); A and C (excluding B); B and C (excluding A); or all of A, B, and C.

[0026] In the following description, all figures disclosed in this application are approximate values, regardless of whether the terms "about" or "approximately" are used in conjunction. They may vary by 1%, 2%, 5%, or sometimes 10% to 20%. Whenever a range of values ​​with a lower limit (RL) and an upper limit (RU) is disclosed, any values ​​falling within that range are specifically disclosed. Specifically, the following values ​​within this range are specifically disclosed: R = RL + k * (RU - RL), where k is a variable ranging from 1% to 100% with a 1% increment, i.e., k is 1%, 2%, 3%, 4%, 5%, ..., 50%, 51%, 52%, ..., 95%, 96%, 97%, 98%, 99%, or 100%. Furthermore, any range of values ​​defined by the two R values ​​as defined above are also specifically disclosed.

[0027] Throughout this specification, references to "implementation," "partial implementation," "one implementation," "another implementation," "specific method," or "partial method" mean that at least one implementation or embodiment in this application includes the specific features, structures, materials, or characteristics described in that implementation or embodiment.

[0028] In this application, numerical ranges are involved. Unless otherwise specified, the numerical ranges mentioned above are considered continuous and include the minimum and maximum values ​​of the range, as well as every value between the minimum and maximum values. Any lower limit can be combined with any upper limit to form a range not explicitly stated; and any lower limit can be combined with other lower limits to form a range not explicitly stated, just as any upper limit can be combined with any other upper limit to form a range not explicitly stated. Furthermore, each individually disclosed point or single value can itself serve as a lower or upper limit and be combined with any other point or single value or with other lower or upper limits to form a range not explicitly stated.

[0029] In lithium-ion electrochemical structures, electrolytes tend to accumulate at the head and tail of the electrode assembly. Especially under external impact, the movement and accumulation of electrolytes significantly increase the risk of internal short circuits. The traditional solution is to place a porous material layer at the end of the cell to adsorb the electrolyte. However, the internal pore structure of such material layers is simple, resulting in unstable permeation paths for the electrolyte when relying on natural diffusion, making it impossible to achieve uniform distribution.

[0030] To address the aforementioned problems, this application proposes an electrochemical device. For example... Figure 1 and Figure 2 As shown, in some embodiments, the electrochemical device includes an electrode assembly 100 and a permeation structure 200, with the permeation structure 200 provided at both the head and tail of the electrode assembly 100. One side of the permeation structure 200 has a gradient pore layer, which comprises multiple porous layers 210, each containing adsorption pores. Along the direction away from the electrode assembly 100, in two adjacent porous layers 210, the adsorption pore size in the porous layer 210 closer to the electrode assembly 100 is A, and the adsorption pore size in the porous layer 210 farther from the electrode assembly 100 is B, satisfying A > B.

[0031] It is understandable that a gradient pore layer refers to a composite structure formed by the sequential stacking of at least two porous layers 210 with different pore sizes, and the adsorption pore size refers to the equivalent diameter of the pores inside the porous layer 210.

[0032] It is understood that the electrode assembly 100 may adopt a spiral or laminated structure formed by a positive electrode, a negative electrode and a separator, which is common in the art. The positive and negative electrodes are provided with tabs, which are led out through the electrode post on the housing 300. This application will not describe this in detail.

[0033] In this embodiment, the adsorption pores generate capillary adsorption forces. The porous layer 210 with larger pore sizes closer to the electrode assembly 100 can quickly absorb the accumulated electrolyte, while the porous layer 210 with smaller pore sizes farther away from the electrode assembly 100 uses stronger capillary forces to migrate the electrolyte outward, accelerating the diffusion of the electrolyte at the head and tail and improving the electrolyte penetration efficiency. As the electrolyte passes through different pore size layers sequentially in the gradient pore layer, it is driven by gradually increasing capillary forces, forming a directional flow from the large pore size region to the small pore size region. This avoids the disordered diffusion of the electrolyte in a single pore structure, making the distribution of the electrolyte in the end region of the electrode assembly 100 more uniform and avoiding the formation of local dry areas.

[0034] In some embodiments, the gradient pore layer can be achieved by uniformly mixing 70 wt% polypropylene (PP) resin, 15 wt% ultra-high molecular weight polyethylene (UHMWPE), and 15 wt% calcium carbonate microparticles, and then melt-extruding the mixture at 180°C to 210°C to form a film with a thickness of 25 μm to 50 μm. The film is then treated with a three-stage stretching process to form the gradient pore structure. Specifically, the film is longitudinally stretched at 90°C to 100°C with a stretching ratio of 2.5:1 to form a first porous layer 210, in which the pore size of the adsorption pores is 2μm to 5μm. It is then longitudinally stretched at 110°C to 120°C with a stretching ratio of 1.5:1 to form a second porous layer 210, in which the pore size of the adsorption pores is 1μm to 2μm. Finally, it is transversely stretched at 130°C to 140°C with a stretching ratio of 3:1 to form a third porous layer 210, in which the pore size of the adsorption pores is 0.5μm to 1μm. The film after the three-stage stretching process is then heat-treated at 150°C for 2 to 5 minutes to fix the adsorption pore structure, forming a gradient pore layer.

[0035] For ease of description, the side of the film closest to the electrode assembly 100 is defined as the inner side, and the other side as the outer side. In the low-temperature stage, i.e., at 90°C to 100°C, the PP / UHMWPE molecular chains partially untangle, and longitudinal stretching forms inner macropores. In the high-temperature stage, i.e., at 130°C to 140°C, the molecular chains completely relax, and transverse stretching forces the pores to compress oriented, forming outer micropores. The difference in stress direction between longitudinal and transverse stretching causes the pores to deform along different dimensions, forming adsorption pores.

[0036] The positions of the inner and outer layers of the pores are achieved through the processing sequence and thermodynamic gradient. The difference in the mobility of polymer molecular chains at different temperatures leads to staged pore formation. In the low-temperature stage, the temperature of the film core lags behind the surface, and the core undergoes plastic deformation first to form large pores. During high-temperature transverse stretching, the surface area is preferentially heated, and the molecular chains rearrange rapidly to close the pores.

[0037] Based on the above embodiments, the porosity of the adsorption pores in each porous layer 210 is 30% to 50%. Porosity refers to the proportion of the volume of pores inside the material to the total volume of the material. When the porosity is less than 30%, insufficient connectivity of the pores inside the material can easily lead to obstruction of the electrolyte permeation path; when the porosity is greater than 50%, the internal support structure of the material can easily weaken and interlayer collapse can easily occur. By limiting the porosity to the range of 30% to 50%, the porous materials in each layer can form a stable three-dimensional network structure while maintaining the pore size gradient distribution.

[0038] The porosity of the porous membrane is 30% to 50%. For example, the porosity of the porous membrane can be 30%, 31%, 32%, 33%, 34%, 35%, 36%, 37%, 38%, 39%, 40%, 41%, 42%, 43%, 44%, 45%, 46%, 47%, 48%, 49%, 50%, or within any two of the above values.

[0039] In the case where the gradient pore layer has three porous layers 210, the porosity of the outer porous layer 210 can be set to 45%, the porosity of the middle porous layer 210 can be set to 35% to 40%, and the porosity of the inner porous layer 210 can be set to 30%. The pore size of the adsorption pores in the porous layer 210 gradually decreases from the inside to the outside, and the porosity of the porous layer 210 gradually increases from the inside to the outside, thereby increasing the capillary adsorption force formed by the gradient pore layer by 3 to 5 times and further improving the adsorption efficiency of the electrolyte.

[0040] From the inside out, the pore size range of the adsorption pores can be sequentially set to 2μm to 5μm, 1μm to 2μm, and 0.5μm to 1μm. Compared with a uniform pore size structure, the electrolyte permeation uniformity is improved by 42%, and the accumulation of electrolyte in the head and tail regions is reduced by 57%. In a 1.2-meter drop test, the short-circuit incidence rate of the electrochemical structure sample using the gradient pore size structure is reduced by 65%.

[0041] Furthermore, the gradient pore layer also includes an adsorption conditioning layer 220, which is located at the difference in the gradient pore layer's distance from the electrode assembly 100. The contact angle between the adsorption conditioning layer 220 and the electrolyte is set to be inversely proportional to the volume of electrolyte in contact with the adsorption conditioning layer 220. By utilizing the characteristic that the contact angle changes with the electrolyte volume, the contact angle is reduced when the electrolyte volume is high to enhance permeation and diffusion, while the contact angle is increased when the electrolyte volume is low to suppress excessive permeation. This achieves dynamic control of the electrolyte permeation rate between the gradient pore layer and the support layer 230, effectively preventing uneven permeation or localized accumulation of electrolyte due to changes in electrolyte volume, and improving the electrolyte distribution stability of the electrochemical device under drop impact or operating condition fluctuations.

[0042] Specifically, in the standard electrolyte, 1M LiPF6 in an EC / DMC ratio of 1:1, the initial contact angle is 75°. As the electrolyte penetration time increases, the contact angle decreases to 35°, demonstrating adjustable adsorption capacity. That is, when excessive electrolyte accumulates, the adsorption regulating layer 220 exhibits strong hydrophilicity; when the electrolyte is uniformly distributed, the adsorption regulating layer 220 exhibits moderate hydrophobicity, thereby maintaining the dynamic balance of the electrolyte and achieving adaptive regulation of the electrolyte.

[0043] In practical applications, the adsorption regulating layer 220 can be configured as a composite coating of polyvinylidene fluoride (PVDF) and nano-silica. PVDF is a fluorine-containing polymer, specifically a powder material prepared using suspension polymerization. The fluorine atoms in the molecular chain impart hydrophobicity and chemical resistance to the material. Nano-silica refers to silica particles with a nanoscale particle size, specifically spherical particles prepared using the sol-gel method. Its surface hydroxyl groups can form chemical bonds with PVDF. The composite coating refers to a heterogeneous structure formed by blending PVDF and nano-silica. It can be applied to the substrate surface using spraying or impregnation processes. PVDF acts as the continuous phase, providing mechanical support, while nano-silica acts as the dispersed phase, forming the surface micro / nano structure.

[0044] After 200 cycles at 55°C, the electrolyte uniformity in the head and tail regions of the electrochemical device with an adsorption structure featuring an adsorption conditioning layer 220 improved by 38%, and the capacity retention of the electrochemical structure increased by 6.3%. At -20°C, the initial discharge capacity of the electrochemical structure increased by 8.1%, demonstrating excellent low-temperature performance.

[0045] In some embodiments, the adsorption conditioning layer 220 can be prepared by: mixing 70 wt% PVDF resin, 30 wt% nano-silica powder and N-methylpyrrolidone (NMP) solvent evenly, and stirring at room temperature for 12 hours to form a uniform slurry; uniformly coating the coating slurry on the surface of the side where the small-pore porous layer 210 is located using a doctor blade coating method, controlling the wet film thickness to be 10 μm to 20 μm; drying at 80°C for 2 hours to remove the solvent; heat-treating at 120°C for 30 minutes to improve the bonding strength between the coating and the substrate; and cooling to room temperature to obtain a gradient porous layer with a functional coating.

[0046] The surface roughness of the polyvinylidene fluoride (PVDF) and nano-silica composite coating dynamically adjusts with changes in electrolyte volume. When the electrolyte volume increases, liquid penetrates the gaps between nanoparticles, reducing surface energy and decreasing the contact angle, thus enhancing penetration. Conversely, when the electrolyte volume decreases, the gaps between nanoparticles recover, forming a high-roughness surface, increasing the contact angle and inhibiting excessive penetration. The PVDF body fixes the nanoparticle positions through chemical bonds, preventing the adsorption regulating layer 220 from collapsing under electrolyte scouring. Simultaneously, the hydrophobic properties of the PVDF body and the wetting regulation of the nano-silica work synergistically, achieving a negative correlation between the contact angle and electrolyte volume.

[0047] In some embodiments, the electrochemical device further includes a housing 300, an electrode assembly 100 disposed within the housing 300, and a permeation structure 200 further includes a support layer 230 disposed on the side of the gradient pore layer opposite to the electrode assembly 100, with the support layer 230 in contact with the housing 300. Specifically, the support layer 230 is arranged between the gradient pore layer and the housing 300, and is in direct contact with the housing 300. When external pressure is applied to the housing 300, the support layer 230 uniformly distributes the pressure throughout the housing 300, preventing deformation of the adsorption pore structure due to localized pressure in the gradient pore layer. In drop impact scenarios, the support layer 230 absorbs impact energy through the deformation buffering effect of its mesh structure, preventing relative displacement between the gradient pore layer and the housing 300. Simultaneously, the support layer 230 also restricts the microscopic deformation of the gradient pore layer during electrolyte permeation, ensuring that the adsorption pore size gradient of each porous structure is maintained.

[0048] Based on the above embodiments, the support layer 230 includes multiple support ribs, which are arranged in an interlaced manner to form a grid structure. The spatial topological characteristics of the grid structure enable the support layer 230 to maintain its morphological integrity during the electrochemical structure assembly process, ensuring the continuous function of the capillary adsorption of the gradient pore layer and preventing local accumulation of electrolyte caused by deformation of the support layer 230.

[0049] Specifically, the grid structure has multiple mesh openings, which can be regular or irregular geometric shapes such as triangles, quadrilaterals, and hexagons. This application does not limit this.

[0050] The staggered arrangement of the supporting ribs forms a continuous and interconnected mechanical transmission path, constructing a three-dimensional load-bearing network between the electrochemical structural shell 300 and the gradient porous layer. When subjected to external pressure, the mesh structure absorbs energy through the deformation of the supporting units surrounding the mesh openings, preventing stress concentration from damaging the capillary structure of the porous layer 210. Simultaneously, the mesh area maintains the integrity of the electrolyte flow channels, allowing the electrolyte adsorbed in the gradient porous layer to diffuse uniformly along the mesh gaps. This structure achieves mechanical support while maintaining the pore connectivity required for electrolyte permeation.

[0051] Furthermore, the width of the support rib can be set to 15μm to 30μm, and the thickness of the support rib can be set to 5μm to 15μm; the support layer 230 has multiple mesh holes, and the side length of each mesh hole can be set to 100μm to 200μm.

[0052] The width of the support rib refers to the lateral dimension of a single rib forming the grid structure in the planar direction, the thickness of the support rib refers to the vertical height of a single rib forming the grid structure, and the side length of the mesh refers to the length of each side of a single grid unit enclosed by the support ribs. Specifically, it can be controlled by adjusting the spacing of the support ribs.

[0053] Supporting ribs with widths ranging from 15 μm to 30 μm form narrow physical boundaries, while side lengths of 100 μm to 200 μm construct a continuous channel network. Under capillary action, the electrolyte preferentially flows along the low-resistance, wide-spacing regions, while the supporting ribs act as guide walls to restrict lateral diffusion. Furthermore, the thin-layer design of 5 μm to 15 μm significantly increases the electrolyte's penetration resistance in the thickness direction compared to flow within the grid plane, forcing the electrolyte to diffuse primarily within the grid plane and preventing large accumulations in any particular area.

[0054] The contact angle between the support layer 230 and the electrolyte is greater than or equal to 70°. By controlling the contact angle range, a hydrophobic interface is formed on the surface of the support layer 230. When the electrolyte contacts the support layer 230, the surface tension of the support layer 230 is greater than the solid-liquid adhesion force, preventing droplets from spontaneously spreading on the surface of the support layer 230. The electrolyte preferentially flows along the gaps in the grid formed by the support ribs, while the gradient porous layer guides the electrolyte longitudinally through capillary adsorption. The synergistic effect of the hydrophobic support layer 230 and the gradient porous layer ensures that the electrolyte is evenly distributed within the grid plane, preventing structural failure due to excessive penetration in localized areas.

[0055] In some embodiments, the support layer 230 can be prepared by: mixing 25 wt% polyamic acid with 75 wt% N,N-dimethylacetamide (DMAC) to prepare a polyimide precursor solution; printing the polyamic acid solution onto a temporary substrate according to preset grid parameters, such as a support rib width of 25 μm and a grid spacing of 150 μm; pre-drying at room temperature for 2 hours to remove some of the solvent; and heat-treating at 150°C for 1 hour to complete the imidization reaction and form a polyimide microgrid structure, i.e., the support layer 230.

[0056] The prepared microgrid structure was transferred onto the adsorption conditioning layer 220 of the gradient pore layer, and a strong bond was achieved between the two using a hot-pressing process. The hot-pressing parameters could be set to 180℃ temperature, 10MPa pressure, and a holding time of 30 seconds.

[0057] With the addition of the support layer 230, the tensile strength of the permeable structure 200 is increased by 85%, making it less prone to tearing or deformation during the assembly and use of the electrochemical structure. In drop tests, after the electrochemical structure underwent 100 consecutive drops from a height of 1.2 meters, the probability of internal short circuits decreased by 78%, and the electrolyte distribution uniformity improved by 62%.

[0058] It is understood that, since the grid structure of the support layer 230 forms a channel that runs through the front and back along the length of the electrode assembly, the inner side of the housing 300 can be insulated, or an insulating layer can be provided on the outer side of the support layer 230. This application does not limit this.

[0059] The permeation structure 200 of the electrochemical device includes a first part 201 and a second part 202. The second part 202 is connected to the edge of the first part 201. The first part 201 is located at the head and / or tail of the electrode assembly 100, and the second part 202 is located on the outer periphery of the electrode assembly 100. The first part 201 of the permeation structure 200, located at the head or tail of the electrode assembly 100, directly targets the problem of electrolyte accumulation at the ends in conventional technologies by performing directional adsorption. The second part 202 extends to the outer periphery of the electrode assembly 100 through edge connection, forming an adsorption area covering the sides. This design allows the electrolyte to diffuse outward through a continuous adsorption interface after being adsorbed at the ends, avoiding local accumulation. At the same time, the second part 202 actively adsorbs the electrolyte in the peripheral area, suppressing lateral migration of the electrolyte caused by gravity or mechanical impact, thereby achieving a balanced electrolyte distribution in three-dimensional space.

[0060] In practical applications, the permeation structure 200 can be formed by wrapping the electrode assembly 100 with adhesive tape. Specifically, the tension of the adhesive tape is controlled within the range of 0.8N to 1.2N, and it is wound 2-3 times, fixed with hot melt adhesive, and heat-treated at 60°C for 30 minutes to improve its adhesion to the battery cell.

[0061] In addition, this application also proposes an electronic device, which includes the electrochemical device described above, and the electrochemical device serves as a driving source or energy storage source for the electronic device.

[0062] The electronic device described in this application is not particularly limited and can be applied to any electronic device known in the prior art. According to some embodiments of this application, the electronic device includes, but is not limited to, mobile phones, smartphones, laptops, tablets, wearable devices, smartwatches, smart bracelets, smart glasses, power banks, televisions, game consoles, game controllers, digital cameras, smart speakers, headphones, keyboards, mice, monitors, drones, audio equipment, home appliances, toys, power tools, automobiles, motorcycles, electric bicycles, bicycles, robots, robot dogs, industrial robots, android robots, etc.

[0063] Although illustrative embodiments have been demonstrated and described, those skilled in the art should understand that the above embodiments should not be construed as limiting the present application, and that changes, substitutions and modifications can be made to the embodiments without departing from the spirit, principles and scope of the present application.

Claims

1. An electrochemical device, characterized in that, include: A permeable structure with a gradient pore layer on one side, the gradient pore layer comprising multiple porous layers, each of which contains adsorption pores. The electrode assembly has the aforementioned permeation structure at its head and / or tail. Wherein, along the length direction away from the electrode assembly, in any two adjacent porous layers, the size of the adsorption pore in the porous layer closer to the electrode assembly is A, and the size of the adsorption pore in the porous layer away from the electrode assembly is B, satisfying A > B.

2. The electrochemical device according to claim 1, characterized in that, In each of the porous layers, the porosity of the adsorption pores is 30% to 50%.

3. The electrochemical device according to claim 1, characterized in that, The gradient pore layer further includes an adsorption conditioning layer, which is disposed on the side of the gradient pore layer away from the electrode assembly; The contact angle between the adsorption conditioning layer and the electrolyte is set to be inversely proportional to the volume of the electrolyte in contact with the adsorption conditioning layer.

4. The electrochemical device according to claim 3, characterized in that, The adsorption regulating layer is configured as a composite coating of polyvinylidene fluoride and nano-silica.

5. The electrochemical device according to claim 1, characterized in that, The electrochemical device also includes a housing, and the electrode assembly is disposed within the housing; The permeation structure further includes a support layer disposed on the side of the gradient pore layer opposite to the electrode assembly, and the support layer is in contact with the housing.

6. The electrochemical device according to claim 5, characterized in that, The support layer includes multiple support ribs, which are arranged in an interlaced manner to form a grid structure.

7. The electrochemical device according to claim 6, characterized in that, The width of the support rib is 15μm to 30μm, and the thickness of the support rib is 5μm to 15μm; The support layer has multiple mesh openings, with each side of the mesh opening having a length of 100μm to 200μm.

8. The electrochemical device according to claim 6, characterized in that, The contact angle between the support layer and the electrolyte is greater than or equal to 70°.

9. The electrochemical device according to claim 1, characterized in that, The permeation structure includes a first part and a second part, the second part being connected to the edge of the first part, the first part being located at the head and / or tail of the electrode assembly, and the second part being located on the outer periphery of the electrode assembly.

10. An electronic device, characterized in that, Includes the electrochemical device as described in any one of claims 1 to 9.